The costs and benefits of deep brain stimulation in Parkinson's disease: a review and social network analysis - Zúñiga-Ramírez, Carlos; Farías-Moreno, Katia Carmina; Moreno, Gabriel; Gómez-Figueroa, Enrique; Caicedo-Ortíz, Hernando Efraín; Carrillo-Ruíz, José Damián (Arquivos de Neuro-Psiquiatria, 2025)
Parkinson's disease (PD) is the second most prevalent neurodegenerative disorder worldwide. Levodopa has been considered the best treatment option. However, deep brain stimulation (DBS) use has increased over time, mostly when levodopa-related complications arise.To review the current evidence regarding economic evaluations assessing costs and benefits comparing pharmacological versus surgical treatment among subjects with PD.We searched three databases (PubMed, Embase, and Google Scholar) for studies comparing levodopa treatment and DBS among subjects with PD in terms of costs and benefits from therapy.Out of the 107 studies identified, 14 met the inclusion criteria. Most of the published studies were from Europe. Incremental cost-effectiveness ratios have shown variable results, from -€979 to €6,729 per change of 1 point in the score on part III of the Unified Parkinson's Disease Rating Scale (UPDRS III), while incremental cost-utility ratios depict values as low as €6,700 and as high as $704,906.03 per quality-adjusted life-years (QALY).We observed a higher cost during the 1st year of DBS implantation due to the surgical procedure itself, subsequently, there was a trend for a lower cost over the following years, with no loss of benefit. Overall, the studies showed DBS as a cost-effective measure at 5-years after implantation.
Keywords: Parkinson Disease; Levodopa; Deep Brain Stimulation; Cost-Effectiveness Analysis; Cost-Benefit Analysis